Microwave ring circuits and related structures - Chang, Kai (J. Wiley, 2004)
For the past three decades, the ring resonator has been widely used in such applications as measurements, filters, oscillators, mixers, couplers, power dividers/combiners, antennas, and frequency-selective surfaces, to name just a few. The field has continued to expand, with many new analyses, models, and applications recently reported.